Exposing Household Cost Accountability Practices: A Study Of Islamic Ethnomethodology - Mohamad Anwar Thalib (The ES Accounting And Finance, 2022)
This study aims to reveal household cost accountability practices conditional on non-material values. This study uses an Islamic paradigm with an Islamic ethnomethodology approach. There are five stages of data analysis: charity, knowledge, faith, revealed information, and good deeds. The study found that accountability for household expenses was carried out by directly conveying the use of costs, showing the items purchased, and showing records of household expenses. The practice of accountability for household expenses is conditional on the value of trust and mutual trust between husband and wife. These two values are a manifestation of their obedience to God's commands